ANALYSIS OF VISUAL INSPECTION WITH ACETIC ACID SCREENING BEHAVIOR AMONG WOMEN OF REPRODUCTIVE AGE AT MUARA ENIM PUBLIC HEALTH CENTER - Desi Marina, Ervita; Ali Harokan; Lilis Suryani; Dewi Suryani (LPPM STIKES Al-Ma'arif Baturaja, 2025)
IVA examination is a screening examination of the post-smear smear because it is usually cheap, practical, very easy to do with simple equipment. This study aims to determine the factors related to the Behavior of IVA Test Examination in Women of Childbearing Age at the Muara Enim Health Center, Muara Enim Regency in 2025.The design of this study is quantitative with a cross-sectional approach. The population in the study were some women of childbearing age (WUS) at the Muara Enim Health Center, Muara Enim Regency in 2024, totaling 12,203 respondents. The sample in this study amounted to 94 people. The sampling method used Purposive sampling. This research was conducted on April 21- May 2, 2025.. Data collection using a questionnaire. Bivariate data analysis using the Chi-Square test and multivariate logistic regression. The results of the study showed that there was a relationship between knowledge (p value 0.00), husband's support (p value 0.02) and the role of cadres (p value 0.00) on the Behavior of IVA Test Examination in Women of Childbearing Age at the Muara Enim Health Center, Muara Enim Regency in 2025. There is no relationship between age (p value 0.13), education (p value 0.99), parity (p value 0.68) and attitude (p value 0.72) with the behavior of IVA Test Examination in Women of Childbearing Age at the Muara Enim Health Center, Muara Enim Regency in 2025. The dominant factor in IVA Test Examination Behavior in Women of Childbearing Age is husband's support (p Value 0.04). For the health center, it can provide health education to women of childbearing age, involve health cadres in various health services in the community including IVA test examination services and provide motivation to families in the IVA test examination